Meditations on first philosophy in focus - Descartes, René, 1596-1650 (Routledge philosophers in focus series., 1993)
This includes the excellent translation by Haldane and Ross of Descartes' Meditations on First Philosophy, an introduction by Tweyman, and six articles indicating the diversity of scholarly opinion on method in Descartes' philosophy.